Estrategias lúdicas y su incidencia en el desarrollo socioafectivo en niños de educación inicial 2 - Montoya Montero, Yamilex Marina (2024)
The present study is based on playful strategies and their impact on the socio-affective development in children of initial education II. It is important to indicate that this work will be developed with the objective of analyzing recreational strategies and their impact on socio-affective development. Initial education is a crucial stage in the comprehensive development of children, where the foundations are established for their cognitive, emotional and social growth. In this context, playful strategies have been highlighted as effective pedagogical instruments to enhance social and affective development in preschool students. The present study will be based on lines of research study from the university; Education and social development, in reference to the research line of the faculty, is based on; Human talent education and teaching in terms of the research line of the career refers to; Motivation and self-regulation in educational contexts and, finally, research subline; play as a construct and psychomotor skills. In reference to methodology, the type of research that could be appropriate for this topic is basic, with a mixed investigative aspect. Which will be based on a non-experimental design because both variables were manipulated (Borja & Benavides, 2020, page 82). For the development of this study, a questionnaire and observation sheets will be applied as an instrument that will allow data to be collected from the research subjects and subsequent analysis and interpretation of the data. In reference to the study techniques, an observation and interview sheet will be applied, as a research instrument, 1 questionnaire will be developed for the observation sheet and 1 open question questionnaire for the interview, the study population will be 16 students, 16 parents family and 6 teachers from the initial area, the same number that will be used as the study sample, that is, the 38 participants analyzed in the population.